Recharge mechanism and salinization processes in coastal aquifers in Nam Dinh province, Vietnam - Hoang Van, Hoan; Larsen, Flemming; Pham Quy, Nhan; Tran Vu, Long; Nguyen Thị Thanh, Giang (Vietnam Journal of Earth Sciences, 2022)
In Nam Dinh province, in the Red River delta plain in Northern Vietnam, groundwater in the shallow Holocene aquifer shows elevated total dissolved solids up to 35 km from the coastline, indicating a saltwater intrusion from the Gulf of Tonkin. High groundwater salinities have been encountered below and adjacent to the Red River in the deep Pleistocene aquifer. Since 1996, large-scale groundwater abstraction was initiated from the deep aquifer, and the observed elevated salinities now raise concerns about whether the groundwater abstraction is undertaken sustainably. We have conducted a study to obtain a fundamental understanding of the recharge mechanisms and salinization processes in the Nam Dinh province. A holistic approach with multiple methods including transient electromagnetic sounding and borehole logging, exploratory drilling, sampling and analyzing primary ion and stable isotope compositions of water and pore water, groundwater head monitoring, hydraulic experiments laboratory of clay layers, and groundwater modeling by using the SEAWAT code. Results reveal that saline river water is leached from the Red River and its distributaries into the shallow aquifers. The distribution and occurrence of salty pore water in the Holocene aquitard clay shows that meteoric water has not been flowing through these low permeable clay layers. Marine pore water has, however, been leached out of the Pleistocene clay. When this layer is present, it offers protection of the lower aquifer against high salinity water from above. Salinity as high as 80 % of oceanic water is observed in interstitial pore water of the transgressive Holocene clay. Saltwater is transported into the Pleistocene aquifer, where the Holocene clay is directly overlying the aquifer.